Analisis Percepatan Waktu dan Biaya dengan Metode Crashing pada Pembangunan Gedung Rawat Inap RS. Budi Asih Trenggalek - Nanda, Rohul; Sony Susanto (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
Delays in the implementation of construction projects are often caused by various factors, such as location conditions that are not in accordance with estimates, changes in planning, the influence of weather conditions, and errors in project management. This study aims to evaluate the total duration and cost of the project after the implementation of the policy of increasing working hours in the construction of the Budi Asih Trenggalek Hospital Inpatient Building. The goal is to assess the extent to which additional man-hours can speed up project completion without incurring significant cost increases. Based on the results of the analysis, the project experienced an acceleration of time for 180 days with a total cost of IDR 2,506,360,952 after the increase in working hours was enforced. When compared to the initial planning, the project under normal conditions takes 189 days, with a breakdown of direct costs of IDR 2,231,100,000, indirect costs of IDR 322,270,000, and total project costs of IDR 2,553,370,000. Meanwhile, the results of the acceleration showed a direct cost of IDR 2,504,000,000, an indirect cost of IDR 2,360,952, and a total final project cost of IDR 2,506,360,952 with an implementation duration of 180 days. From the addition of these working hours, it is effective in accelerating the completion of the project without incurring significant costs, in the construction of the building the cost under normal conditions is Rp 2,553,370,000, while the cost in accelerated conditions is Rp 2,506,360,952, so the profit from the cost comparison is Rp 47,009,048,-